Unveiling the Impact of Green Financing and Sustainability Reporting on Indonesian Banks: Two-Fold Analysis using Tobins’Q and RoRWA - Marlene; Nainggolan, Yunieta Anny (Integrasi Sains Media, 2025)
The primary objective of this research is to investigate the two-fold impacts of portfolio Green Financing (GF) and GRI-based Sustainability Reporting Disclosure (SRD) on the financial performance of Indonesian banks. At the focal points of the country’s sustainability transition, banks play a catalytical role in directing capital between environment protection, climate risk policy, societal impact, industry adaptation, and long-term financial resilience. Using a panel data set of 44 IDX-listed commercial banks from 2021-2023, the research applies a dual-lens empirical framework: Tobin’s Q to measure market perception and Return on Risk Weighted Assets (RoRWA) to capture internal regulatory-aligned profitability. The result reveals that Green Finance and Sustainability Reporting Disclosure consistently improved RoRWA, confirming the strategic financial merit of green lending. Nonetheless, Tobin’s Q revealed that GF does not have a substantial effect, suggesting that the market may undervalue banks' sustainable business initiatives. SRD initially demonstrates significance but loses its explanatory power when the full model is introduced, indicating immaturity and narrative-heavy disclosure, which lack integrated rigorous financial materiality. Research emphasizes the importance of aligning SRD transparency and GF execution to accelerate new taxonomy-based reporting, develop RoRWA-linked ESG metrics, and explore potential macro and micro-prudential incentives. This research provides policy and managerial insight to support the scalability of green finance and credible sustainability reporting in Indonesia and other emerging markets.